Wittgenstein and phenomenal concepts - Child, T (Routledge, 2015)
Many philosophers think that there are phenomenal concepts: distinctive ways of thinking of experiences or sensations that can be grasped only by those who know what it is like to have those experiences or sensations. What light does Wittgenstein’s philosophy throw on this idea? In the literature, phenomenal concepts are often deployed for explicitly anti- Wittgensteinian purposes. Brian Loar and Christopher Peacocke, for example, both appeal to phenomenal concepts in arguing, against Wittgenstein, that a person can derive, from her own case, a concept of pain that can be applied to other people.1 And David Papineau and Katalin Balog argue that the existence of phenomenal concepts is inconsistent with Wittgenstein’s arguments against a private sensation language.2 Against these and similar views, I shall argue for the unorthodox view that a Wittgensteinian approach to sensations and sensation language can accommodate a version of the idea that there are distinctive concepts of sensations that are available only to those who know what it is like to have those sensations. For those who are interested in Wittgenstein, that is an important corrective to much that has been thought about the nature of a Wittgensteinian approach to these matters. For those who are interested in phenomenal concepts, my discussion helps to identify exactly what the existence of such concepts does and does not involve.